1998
DOI: 10.1111/j.1528-1157.1998.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome in Patients with Epilepsy with Occult Vascular Malformations Treated with Lesionectomy

Abstract: Summary:Purpose: This retrospective study reports the longterm surgical outcome of patients with medically refractory epilepsy and vascular malformations who were treated with lesionectomy. A detailed analysis of surgical failures had been performed in an attempt to define predictors of surgical success and failure.Methods: Fifteen patients with medically intractable epilepsy and angiographically occult vascular malformations (AOVMs) were treated surgically with lesionectomy at Duke University Medical Center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In a study of 15 patients with occult vascular malformations, Kraemer et al (21) concluded that the removal of the lesion and adjacent hemosiderin was highly effective in treating seizures, as 73.3% of patients were seizure-free postoperatively. The same authors proved experimentally, in other studies, that the gliotic, hemosiderin-laden tissue of vascular malformations was associated with epileptogenic activity (19,20).…”
Section: Outcome Versus Excision Of Surrounding Gliosismentioning
confidence: 99%
“…In a study of 15 patients with occult vascular malformations, Kraemer et al (21) concluded that the removal of the lesion and adjacent hemosiderin was highly effective in treating seizures, as 73.3% of patients were seizure-free postoperatively. The same authors proved experimentally, in other studies, that the gliotic, hemosiderin-laden tissue of vascular malformations was associated with epileptogenic activity (19,20).…”
Section: Outcome Versus Excision Of Surrounding Gliosismentioning
confidence: 99%
“…1,6,7,10,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] Cavernous malformations may not directly generate seizures, 4,39 but it is hypothesized that the area surrounding the malformation, the ''hemosiderin rim'', is the epileptogenic region due to iron deposition from recurrent hemorrhage. 4,[39][40][41] Hence, removing this hemosiderin rim during cavernous malformation surgical resection has been postulated to improve seizure outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, postoperative seizure outcome for these cases is almost as good as that of temporal lobectomies. 21,[31][32][33] This is true for various lesions, and excellent outcomes (seizure-free or almost seizure-free) have been reported in 73 to 83% of cases for vascular malformations, [34][35][36] in 70% of cases for encephalomalacia, 37 and in 63 to 79% of cases for neoplasms. 38,39 Numbers are somewhat lower for cortical dysplasias, ranging from 35 to 42%.…”
mentioning
confidence: 96%